Prevalence of dental fluorosis based on gender predilection - JITESH. S,; DR. JESSY,; MARIMUTHU, DR MADHULAXMI (The journal of contemporary issues in business and government, 2020)
The aim is to assess the gender predilection of dental fluorosis among the Chennai population. The retrospective study done using case records of patients. Patients with dental fluorosis were included in this study. Patients who were medically compromised and with other developmental anomalies of teeth were excluded from the study. Data about the dean fluorosis index and demographic details were retrieved from case sheets and tabulated. Analysis of the data was performed using SPSS version 23.0, both descriptive statistics and Chi square tests were performed. The present study showed the dental fluorosis was more prevalent in males (69.20%) than females (30.80%). Among the study population,mild fluorosis(50%) was found to be a more common type of severity of fluorosis followed by moderate fluorosis(30%) and there was significant association between the severity of fluorosis i.e dean fluorosis index and gender (p < 0.05 ) showing statistical significant difference. Within the limits of the present study, it can be concluded that dental fluorosis is more prevalent among males than females. Mild fluorosis was found to be a more common type of severity of fluorosis followed by moderate fluorosis and there was significant association between the severity of fluorosis and gender.